The customer spending map: A framework for omnichannel excellence - Thomas Rudolph; Matthias Eggenschwiler; Andreas Hauschke (Marketing Review St.Gallen, 2025)
As omnichannel shopping is becoming the norm, new tools are required for managing customer touchpoints. This article introduces a novel customer-oriented framework that combines three important levels of customer journey analysis. By identifying eight mutually exclusive customer segments, the customer spending map enables omnichannel managers to steer customer journeys more profitably.
Keywords: 650